(untitled) (Construction Economics and Building, 2019)
Prequalification (PQ) is a significant process in the selection of private sector for the delivery of civil infrastructure projects. But, the extant literature, for the most part, focused on PQ of construction projects. The need for setting proper PQ, i.e., criteria and corresponding limits in public-private partnership (PPP) infrastructure projects, especially municipal solid waste (MSW) projects is still a lacuna in the body of knowledge of Indian PPPs. To this end, this paper identified PQ criteria using content analysis of the sample of MSW projects. These identified criteria were subjected to regression modeling. These results were compared with the results of well-matured highway sector to draw comparison with MSW projects. The practical implications are that urban local bodies (ULBs) are but less competent and less uniform in the rationale of setting the PQ criteria and limits. This paper suggests that lowering the technical and financial PQ limits considering the market orientation will help in bringing more competitive bidders into the bidding. Since MSW is in a very nascent stage of application of PPP, the study results could lay directions for future project procurement to discern right limits for right project sizes.